A Coasian boundary inquiry on zoning and property rights: Lot and zone boundaries and transaction costs. (November 2017) - Lai, Lawrence W.C.; Davies, Stephen N.G.
Highlights: Original interdisciplinary attempt to relate modern zoning to private property rights boundary delineation. New angle to connect penumbrality of zonal and exactitude of property boundaries. Real world examples and extant literature to support arguments. Abstract: Coase's (1960) famous story of land use conflicts between two farms, as generalized in the Coase Theorem, injects into neo-institutional economics a potential to overcome the a-spatial limitations of neo-classical economics and contribute to theorization in planning as a science for delineating places for specific purposes, or zoning. In the light of the historical evolution in spatial division of labour and a review of the literature on the definitions and meaning of zoning, this exploratory interdisciplinary inquiry informed by neo-institutional economics, history of surveying and planning, attempts to use the corollary of the Coase Theorem, which highlights the significance of property boundaries, to explore several boundary scenarios in planned zoning that are of policy significance. They are conflicts of zoning, borderline non-zoning, incomplete zoning, forgotten zones, zoning for non-planning, rights-conferring zoning and co-development zoning. The transaction cost implications of these scenarios are spelled out. Examples from Europe, China, Australia and Americas are cited and elaborated where suitable to illustrate specific arguments.